2005
DOI: 10.1259/bjr/73834093
|View full text |Cite
|
Sign up to set email alerts
|

Radiological characterization of spinocerebellar ataxia type 6

Abstract: Spinocerebellar ataxia type 6 (SCA-6) is a rare, autosomal dominant neurodegenerative condition characterized by adult onset cerebellar ataxia and ocular movement disorders. The presentation is non-specific, and radiological characterization would be of diagnostic benefit. There is little published on the radiological appearances of SCA-6, and there are conflicting reports in the literature. We report the radiological findings in a group of 10 patients with SCA-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
3
18
0
1
Order By: Relevance
“…One previous neuropsychological report of a perceptual timing deficit implicated superior parts of the cerebellum, in particular, the right lateral hemisphere (14). The present study demonstrates a specific deficit in absolute time perception in a group with SCA-6 that experiences stereotyped progression of the cerebellar degeneration from the superior to the inferior parts, especially affecting the vermis (24). Our data are consistent with previous suggestions of a particular role of the superior cerebellum in absolute timing, and suggest a particular importance of the midline cerebellum.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…One previous neuropsychological report of a perceptual timing deficit implicated superior parts of the cerebellum, in particular, the right lateral hemisphere (14). The present study demonstrates a specific deficit in absolute time perception in a group with SCA-6 that experiences stereotyped progression of the cerebellar degeneration from the superior to the inferior parts, especially affecting the vermis (24). Our data are consistent with previous suggestions of a particular role of the superior cerebellum in absolute timing, and suggest a particular importance of the midline cerebellum.…”
Section: Discussionsupporting
confidence: 57%
“…Some inconsistency of the effect in previous studies may reflect the heterogeneity of lesions in these populations of stroke patients (14,15). The current study assessed 34 individuals with a genetically determined, isolated disorder of the cerebellum that advances in a stereotyped way from the superior to the inferior part (24).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…5,7,8 Although Murata et al 8 found a reduction of the anteroposterior diameter of the pons in patients with SCA6, results failed to show a correlation with CAG repeat length. The relationship between the volume changes and clinical dysfunction was not tested in this study.…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3][4][5][6] Particularly, MR imaging has been proved to detect additional extracerebellar involvement in vivo. Several prior MR imaging studies have demonstrated atrophy in SCA6, mainly of the cerebellum, [7][8][9] whereas additional involvement of the cerebral cortex, basal ganglia, pons, and medulla has been identified by using MR imaging in SCA3. 1,4,5,10,11 However, there is increasing evidence of widespread neurodegeneration in SCA6 affecting the brain stem and the primary motor cortex, as shown recently in neuropathologic studies.…”
mentioning
confidence: 99%